2020
DOI: 10.1007/s00795-020-00274-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MUC5AC expression is associated with mismatch repair deficiency and proximal tumor location but not with cancer progression in colon cancer

Abstract: Mucin 5AC (MUC5AC) is a secreted gel-forming mucin expressed by several epithelia. In the colon, MUC5AC is expressed in scattered normal epithelial cells but can be abundant in colorectal cancers. To clarify the relationship of MUC5AC expression with parameters of tumor aggressiveness and mismatch repair deficiency (dMMR) in colorectal cancer, a tissue microarray containing 1812 colorectal cancers was analyzed by immunohistochemistry. MUC5AC expression was found in 261 (15.7%) of 1,667 analyzable colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…MUC5AC expression has been reported in association with expression in microsatellite-unstable/mismatch repair-deficient tumors [21]. Rico et al study showed a strong association of MUC5AC expression with mismatch repair deficiency (dMMR) in colorectal cancers [31]. Kesari et al have reported that MUC5AC expression increased as the stage of disease progressed from 1 to 4 [17].…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC expression has been reported in association with expression in microsatellite-unstable/mismatch repair-deficient tumors [21]. Rico et al study showed a strong association of MUC5AC expression with mismatch repair deficiency (dMMR) in colorectal cancers [31]. Kesari et al have reported that MUC5AC expression increased as the stage of disease progressed from 1 to 4 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the few studies investigating the clinical relevance of MUC5AC expression in other cancer types have also led to discrepant findings. High MUC5AC expression was linked to favorable tumor parameters in gastric and ovarian cancer, 39 unrelated to tumor phenotype in breast and colorectal cancer, 19,[40][41] and linked to an unfavorable phenotype in lung cancers. 42 Based on these findings, it cannot be excluded, that the biological role of MUC5AC expression in cancer cells might be dependent on the tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarray sections were stained and analyzed for MUC5AC as described previously by Rico et al 19 In brief, primary antibody specific against MUC5AC protein (mouse monoclonal, MSVA-109, MS Validated Antibodies, Hamburg, Germany) was applied at 1:200 dilution after antigen retrieval of the tissue sections at 121°C for 5 min in pH 7.8 TRIS-EDTA buffer. Mucin 5AC staining was seen in the membrane and cytoplasm of the cancer cells and immunostaining was interpreted as follows: Negative: no staining; weak: staining intensity of 1 + in ≤ 70% of the tumor cells or staining intensity of 2 + in ≤ 30% of the tumor cells; moderate: 1 + in > 70%, or 2 + in > 30% but in ≤ 70%, or 3 + in ≤ 30% of the tumor cells; strong: 2 + in > 70% or 3 + in > 30% of the tumor cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, MUC5AC was not reported among the core mucus proteins in active UC ( 45 ). MUC5AC is frequently present in colorectal adenomas and colon cancers, thus it’s elevation might be due to UC-induced carcinogenesis ( 48 ).…”
Section: Goblet Cellsmentioning
confidence: 99%